The Common Roles of Fathers: The Five Ps - Garret D. Evans; Kate Fogarty (EDIS)
Fathers play many roles in parenting their children. Some are involved in every facet of their child's life while others concentrate on one or two aspects of raising their child. In the United States, the role of the father has changed, with today's fathers taking more responsibility for raising their children. This document is FCS2140, one of a series of the Family, Youth, and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: December 1999. Revised: August 2005.